Psychological Impact of the COVID-19 Pandemic on Athletes - Uroh, Clifford C.; Adewunmi, Celina M. (Frontiers in Sports and Active Living, 2021)
This study explored the influence of athletic identity and sports participation on the psychological well-being of athletes during a pandemic. The objective of the study was to understand the psychological impact of the coronavirus lockdown measure on athletes who were not able to carry out their normal daily routine. Athletes from nine different sports completed an online survey during the sixth week of the total lockdown in Nigeria. The online survey consists of an athletic identity scale and the Kessler Psychological Distress Scale (K10). Data collected were analyzed using Multiple regression and the Mann-Whitney test at 0.05 level of significance. The result of the findings revealed that category of sports (individual and team) (M = 0.73, β = −6.116) and athletic identity (M = 59.16, β = −0.166) predicts psychological distress to some degree. Few individual sports athletes and athletes with low athletic identity are prone to higher levels of psychological distress than team sports athletes and athletes with high athletic identity during the coronavirus pandemic lockdown. Individual sports athletes reported elevated levels of psychological distress compared to team sports athletes (z = −2.186, p = 0.03, r = 0.27). In conclusion, the results have confirmed that some athletes competing in individual sports experience elevated levels of psychological distress during the coronavirus pandemic, therefore they need the support of a sports psychologist during such periods to help in maintaining their psychological well-being.